SELF-FORMATION OF FEMININITY AND MASCULINITY AND CULTURAL ENVIRONMENT: STUDENTS’ VIEW - Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 2011)
Self-formation of femininity and masculinity of secondary school students and influence of cultural environment to it is being analysed. On the basis of the results of the qualitative study “Identity, cultural transmission, and education” it is shown that femininity and masculinity are being formed in the family basing on the examples of parents (and grandparents). School, friends, the internet and the mass media make secondary influence, mainly providing with information and knowledge which serve as a basis for understanding or modification of gender identity. Education in secondary school is gender-neutral, and results of the research do not give any clue about implementation of the program “Preparation for a family and gender education” to the curriculum. Narratives of the students give too ideal picture of their attitudes towards gender equality which causes some doubts about deepness of understanding gender.